Effective Leadership: A Literature Review of Concepts, Characteristics, and Best Practices - Agustian Zen; Siminto Siminto; Muhammad Ade Kurnia Harahap; Yanto Budi Prasetya; Abu Muna Almaududi Ausat (Universitas Pahlawan Tuanku Tambusai, 2023)
Leadership is one of the key factors that influence organisational success. With increasing global competition and rapid changes in the business environment, effective leadership is increasingly important to maintain organisational competitiveness. The discussion in the purpose of this study will cover several important topics, such as the basic concepts of leadership, characteristics of effective leadership, leadership styles, roles and responsibilities of a leader, and best practices in leadership. The focus of this study is qualitative. Methods for gathering information include paying close attention and taking detailed notes, with subsequent analysis including data reduction, visualisation, and conclusions. The results of the study include a summary that the essential characteristics of effective leadership are having vision, integrity, empathy, communication ability, interpersonal skills, and the ability to motivate and inspire subordinates.